INVENTARISASI ETNOBOTANI TUMBUHAN OBAT YANG DIGUNAKAN MASYARAKAT KENAGARIAN SUNGAI JANIAH - Arfan, Arfan Yuza; Fitri, Rahmadhani (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Background: Ethnobotany is a field of science that studies the reciprocal relationship between humans and plants, medicinal plants are a branch of science from ethnobotany, since ancient times the people of West Sumatra have still used plants as a medium for treatment, one of which is the Kenagarian Sungai Janiah community, Gunung Talang District, Solok Regency, Sumatra Province West. Methods: methods and community interviews about medicinal plants that are often used by the community. This research was conducted in the period November-December 2023. Results: Hasil penelitian yang diperoleh dari penelitian ini adalah tumbuhan yang sering digunakan masyarakat Kenagarian Sungai Janiah sebanyak 16 spesies yang termasuk ke dalam 11 familia. Bagian tumbuhan yang paling sering digunakan masyarakat adalah daun. Conclusion: From the results of the research that has been carried out, it can be concluded that the Kenagarian Sungai Janiah community uses plants as a medium for traditional medicine. The plants commonly used by the community consist of 16 species belonging to 11 families. The parts of plants that people often use are leaves and there are also some who use plant parts in the form of stems, roots, rhizomes and fruit.